The Effect Of Age And Plant Spacing On The Growth And Production Plant Rice (Oryza sativa L.) - Asyita Mufikha; Al Machfud WDP (Nabatia, 2016)
This study aims to determine the effect of the interaction of seed age treatment and planting distance on the growth and production of rice plants. This research was conducted in Lambangan Village, Wonoayu Subdistrict, Sidoarjo Regency, East Java Province and carried out from February 2016 to June 2016. The experiment was arranged factorially using a Randomized Block Design (RBD); first factor: age of seedlings, while the second factor: spacing. Observed variables were plant height, number of tillers, panicles per clump, number of grains per clump, weight of 100 grains, grain wet weight, grain dry weight, dry weight, stover weight and harvest index. The results showed that there was a significant interaction effect on plant height that was 53.09 cm at 50 HST and the number of panicles per clump was 6.89. Seedling age had a significant effect on plant height variables at 50 DAP, 48.73. Whereas plant spacing had a significant effect on the variable number of tillers ie 7.00 at 50 HST, number of grains per clump was 691.22 grains, grain wet weight was 15.68 grams, grain dry weight was 11.70 grams, and dry weight stover is 20.26 grams, the highest production is obtained from the treatment of spacing of 10 cm x 20 cm.